Irgit ethnonym: origin and contemporary state in Mongun-Taiga district of the Republic of Tuva - Syuryunmaa, Ayran Ch. (The New Research of Tuva, 2013)
Article represents a competition work at All-Russian contest of scientific research works of school children "Homeland” (April, 2013).
Keywords: ethnonym; Irgit; Mongun-Taiga; ethnography; history